Clinico-laboratory profile of dengue patients in a tertiary hospital of Eastern India - Murmu, Malati; Singh, Lagendra Kumar; Kamble, Suchita Sambhaji; Dash, Laxmikanta; K. P., Karun Mahesh; Kandathil, Joyal J. (International Journal of Research in Medical Sciences, 2018)
Background: Dengue is the most rapidly spreading mosquito-borne viral disease of mankind. According to WHO, about 50-100 million new dengue infections are estimated to occur annually in more than 100 endemic countries.So, the present study has been done to analyzed varied clinical and laboratory profile of confirm dengue cases. Methods: Cross-sectional observational study was undertaken among 106 adult Ig M Ab positive cases admitted during October 2015 to September 2017. All patients were evaluated clinically and subjected for relevant laboratory investigations. Results: In our study male and female ratio was 20.2:1. Most common symptom was fever (95.3%) and least common was jaundice. Second most symptom was headache (70.8%). Myalgia was present in 49.1% of cases. 54.7% had nausea/vomiting. Hypotension was noticed in 33% of cases whereas encephalopathy and melaena was found in 6.6% and 2.83% respectively. Leucopenia was present in 57.5% and thrombocytopenia in 50.9% of cases. Conclusions: Younger male were commonly affected with dengue fever and promptly responded to conservative therapy due to early confirmation of diagnosis. Mortality was only 1.8% cases, may be due to delay in seeking medical attention.